2021
DOI: 10.3389/fgene.2021.680528
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Differentially Expressed Rhythm Genes in Liver Hepatocellular Carcinoma

Abstract: Liver Hepatocellular Carcinoma (LIHC), a malignant tumor with high incidence and mortality, is one of the most common cancers in the world. Multiple studies have found that the aberrant expression of rhythm genes is closely related to the occurrence of LIHC. This study aimed to use bioinformatics analysis to identify differentially expressed rhythm genes (DERGs) in LIHC. A total of 563 DERGs were found in LIHC, including 265 downregulated genes and 298 upregulated genes. KEGG pathway enrichment and GO analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In recent bioinformatics research, the expression levels of circadian genes were discovered to be closely associated with the tumor microenvironment of non-small cell lung cancer (NSCLC) [ 8 ], and the abnormal expression of circadian genes affected the occurrence and development of glioma by affecting the cell cycle and tumor immune landscape [ 9 ]. Our recent study also identified the differentially expressed rhythm genes CSNK1D/CSNK1E/NPAS2 that were closely linked to the occurrence of liver hepatocellular carcinoma (LIHC) and have the potential to be used as diagnostic biomarkers for patients with LIHC [ 10 ]. However, bioinformatics studies on differentially expressed rhythm genes in KIRC have only rarely been reported [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent bioinformatics research, the expression levels of circadian genes were discovered to be closely associated with the tumor microenvironment of non-small cell lung cancer (NSCLC) [ 8 ], and the abnormal expression of circadian genes affected the occurrence and development of glioma by affecting the cell cycle and tumor immune landscape [ 9 ]. Our recent study also identified the differentially expressed rhythm genes CSNK1D/CSNK1E/NPAS2 that were closely linked to the occurrence of liver hepatocellular carcinoma (LIHC) and have the potential to be used as diagnostic biomarkers for patients with LIHC [ 10 ]. However, bioinformatics studies on differentially expressed rhythm genes in KIRC have only rarely been reported [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancancer analysis indicates that the expression of CSNK1D was correlated to shorter DFS time in multiple cancer types, such as COAD and LIHC, and was dysregulated in various cancers, which was consistent previous reports. For example, Liu et al reported that CSNK1D levels are strongly upregulated in HCC samples [ 41 ]. Upregulation of CSNK1D is associated with a poor prognosis for HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…71 Evidence that the clock machinery is gradually hampered and disrupted in liver disease can be appreciated from hepatocellular carcinoma studies as clock gene expression is markedly altered and associated with survival, recurrence, and other important clinical aspects. 72,73 Indeed, chronodisruption is a commonly found process in many-if not all-types of cancer. [74][75][76][77][78] In summary, there is an important gap in our knowledge regarding how the clock behaves under NAFLD/ NASH conditions.…”
Section: Chron Odi Sru Ption?mentioning
confidence: 99%